El trabajo infantil y su repercusión en el rendimiento académico de los niños de educación básica madia periodo 2016-2017 - Chasi Espinosa, Jorge Neptalí Sarzosa Tonato, Mónica Elizabeth (2017)
This research aimed at diagnosing the child labor and its impact on the students’ academic performance from Basic Middle Level Education “Juan León Mera” Educational Unit. This work arises as a response to a problem that there is in all the schools of the country particularly in this educational unit; where the economic and social crisis affects most of students’ homes, so they are forced to work prematurely. According to the developed methodology, the research is in the quantitative approach, constituting the documentary, bibliographic and the field work the basic modalities of the process; this research corresponded to the descriptive type, because it describes the problem of study how it is, techniques such as the interview and the survey, through instruments such as the question guide and the questionnaire were used for data collection respectively. The results of the project expose great shortcomings in the family responsibility related with their children’s welfare; weaknesses that must be overcome by means of the authorities, teachers and parents’ responsible commitment; empowering the conclusions and punctually assuming the recommendations made in the final report section, so that the project fulfills the purpose, relevance and contribution initially planned.